EFFECTIVENESS OFiMANAGEMENTiINFORMATION SYSTEMSiAND MOTIVATION ONiEMPLOYEE PERFORMANCEiAT PT. BANK SULSELBAR, GOWA BRANCH - Dian Retno Pratiwi; Mahlia Muis; Fauziah Umar (The Scientia Journal of Economics Issues, 2023)
The managementiinformationisystemiis the internal planningisystemiof a companyiwhich includes internalicontrolsisuch asithe useiof resources, documents, technology, and management accounting asioneiof the businessistrategies. Currently, informationitechnology is a dominant factor in implementing information systems as a solution for organizations to solve the problems they face. One of the problems faced by organizations is employee efficiency. If, until now, the organization has not implemented a management information system, this is a sign of decreased employee performance. Reducing employee performance creates irregularities and leads to complaints. One ofithe factorsithat influenceithe increaseiin employeeiperformance is an efficient and effective management information system and work motivation. Thisistudy aimedito determineithe effectiof accuracy, relevance, timeliness, andimotivation oniemployee performanceiat PT. Bank Sulselbar Gowa Branch. Theianalytical methodiused inithis researchiis multipleilinear regressionianalysis, validityitest, reliabilityitest, andipartialitest (t). Theiresearch results show that accuracy, relevance, and timeliness significantly affect employee performance at PT. Bank Sulselbar Gowa Branch.